Studies of the Adsorption Thermodynamics of Oxamyl on Fly Ash - Dhirendra Singh (Adsorption Science & Technology)
The adsorption thermodynamics of oxamyl on fly ash at 10°C, 25°C and 50°C have been studied via the relevant adsorption isotherms, Freundlich constants (K F and 1/n), distribution coefficient (K d ) and other thermodynamic parameters. The data were well fitted by the Freundlich equation (r 2 > 0.98) and yielded S-shaped isotherms at all the temperatures studied. Thermodynamic parameters such as the thermodynamic equilibrium constant (K 0 ), the standard free energy change (ΔG 0 ), the standard enthalpy change (ΔH 0 ) and the standard entropy change (ΔS 0 ) have been calculated as a means of predicting the nature of the adsorption process.